Co-Designing for Equity in Informal Science Learning: A Proof-of-Concept Study of Design Principles - Durall, Eva; Perry, Sophie; Hurley, Mairéad; Kapros, Evangelos; Leinonen, Teemu (Frontiers in Education, 2021)
Informal science learning has great potential to engage diverse learners, but faces issues of persistent inequities. While systemic change is needed to address these issues at a structural level, there is also a need for practical tools to support the organisations and the educators who are working to engage audiences in informal science that is authentic, culturally responsive, interest driven and learner centered. This article presents a collection of design principles, generated through a design approach which actively involved informal science learners, practitioners and researchers from nineteen countries as contributors. We present the design approach adopted, and suggest that participatory design methods could play a role in supporting equity efforts in informal science learning since several of the educators involved in the process decided to adopt participatory methods in their own practice. We also present an overview of the design principles generated through this process, and discuss the application of an early draft of these in an authentic informal science education programme. By adopting and adapting these principles and approaches in their practices, educators can work towards creating equitable and transformative informal science learning environments and experiences.